Desenvolvimento de blendas poliméricas de PLA/Amido e PVDF/Amido para aplicações como biomateriais - Pereira, João Domingos Augusto dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Foams of PLA/Starch and PLA/Starch/Sepiolite (SEP) with different compositions were produced. The following techniques were used in the samples characterization: i) scanning electron microscopy (SEM); ii) density (ρ) measures; iii) differential scanning calorimetry (DSC), iv) mechanical analysis (flexion and traction); v) dynamic mechanical thermal analysis (DMTA); vi) in vivo test. In the SEM images, in both foams and precursors, the interface between the phases was eminently physic with two distinct phases with gaps between them, and an increase in size of the gaps was observed in the foam. It was observed that in the samples with SEP occurred greater generation of smaller cell and more compact. This demonstrates that SEP presented, as well as the starch granules, the nucleating agent behavior. In ρ measures the lowest values were found in samples originating from the autoclave and glycerine bath, respectively. These decreases were consistent with the expansion of PLA matrix observed in the SEM images. In the DSC measurements in general, the starch addition to PLA resulted in increased Xc. This effect happened because the interface between starch and PLA be more energetic, which facilitated the crystals formation in the PLA matrix. In composites containing SEP, generally larger Xc values were observed when compared with the PLA/starch blends in the same proportions materials. This behavior is probably related to the effect of the SEP as a nucleating agent in the PLA. In the mechanical analysis, flexion and traction, with increasing starch content in the blends lower resistance and maximum deformation as the tension and rupture deformation were obtained. Additionally, the same decrease in performance was maintained for composites SEP. However, in the tensile test, these samples showed values greater than the blends. In the results observed via DMTA, in general, the addition of starch and SEP resulted in a stiffness decrease of PLA matrix, that is, E' lower values for blends and composites when compared with pure PLA samples. In the in vivo study, approved by the Ethics Committee on Animal Use the FCT/UNESP, Presidente Prudente, São Paulo, Brazil (process No. 02/2014), 18 rats Wistar (Rattus norvegicus, albino variety, Rodentia, Mammalia) were used with age of 120 days, obtained from the Universidade do Oeste Paulista (UNOESTE). The animals underwent surgical procedure for samples implantation, after 40 weeks counted from the implantation surgery date, the samples were removed. For structural analysis of removed samples and tissues SEM morphology measurements and optical microscopy (OM) were performed respectively. It was observed by SEM technique that the surfaces of post-implant samples showed a pattern coating by biological tissue with capsular morphology. In the photomicrographs obtained by OM, structures such as muscle fibers; adipose tissue (AT) and dense connective (TDC) were observed. Furthermore, in photomicrographs were observed in some few focal inflammatory infiltrate. Next to the muscle tissue was observed the presence of AT permeated by the TDC, featuring as capsular tissue.

Espumas de PLA/Amido e PLA/Amido/Sepiolita (SEP) com distintas composições foram produzidas. As amostras foram caracterizadas pelas seguintes técnicas: i) microscopia eletrônica de varredura (MEV); ii) medidas de densidade (ρ); iii) calorimetria diferencial exploratória (DSC), iv) análise mecânica (flexão e tração); v) análise térmica dinâmico mecânica (DMTA); vi) testes in vivo. Nas imagens de MEV, tanto nos precursores quanto nas espumas, a interface entre as fases foi eminentemente física com duas fases distintas e houve ocorrência de lacunas entre elas, sendo que um aumento no tamanho das lacunas foi observado nas espumas. Observou-se que nas amostras com SEP ocorreu uma maior geração de células com menores dimensões e mais compactas. Isto demonstra que a SEP apresentou, assim como os grânulos de amido, o comportamento de agente de nucleação. Nas medidas de ρ os menores valores ocorreram com as amostras originárias do autoclave e do banho de glicerina, respectivamente. Essas diminuições foram consistentes com a expansão da matriz de PLA observada nas imagens de MEV. Nas medidas de DSC, em geral, a adição do amido ao PLA implicou no aumento da Xc. Tal efeito sucedeu-se devido a interface entre o amido e o PLA ser mais energética, o que facilitou a formação de cristais na matriz de PLA. Nos compósitos contendo SEP, em geral, maiores valores de Xc foram observados quando comparados com as blendas de PLA/amido nas mesmas proporções de materiais. Esse comportamento provavelmente está associado ao efeito da SEP como agente nucleante no PLA. Na análise mecânica, tanto no ensaio de flexão quanto no de tração, com o aumento do conteúdo de amido nas blendas menores foram a resistência e a deformação máxima, bem como a tensão e a deformação de ruptura. Adicionalmente, o mesmo comportamento de diminuição foi mantido para os compósitos com a SEP. No entanto, no ensaio de tração, essas amostras apresentaram medidas com valores maiores do que o das blendas. Nos resultados observados via DMTA, em geral, a adição do amido e da SEP diminuíram a rigidez da matriz PLA, ou seja, valores de E' menores nas blendas e nos compósitos do que nas amostras de PLA puro. No estudo in vivo, aprovado pela Comissão de Ética no Uso de Animais da FCT/UNESP, Presidente Prudente, São Paulo, Brasil (processo nº 02/2014), foram utilizados 18 ratos machos da linhagem Wistar (Rattus novergicus, variedade albina, Rodentia, Mammalia) com idade de 120 dias, obtidos junto à Universidade do Oeste Paulista (UNOESTE). Os animais foram submetidos a processo cirúrgico para a implantação das amostras e após 40 semanas, contadas a partir da data da cirurgia de implantação, as amostras foram removidas. Para a análise da morfologia estrutural das amostras e tecidos removidos, medidas de MEV e microscopia ótica (MO) foram realizadas, respectivamente. Observou-se pela técnica de MEV que as superfícies das amostras pós implante apresentaram um padrão de recobrimento por tecido biológico com morfologia capsular. Nas fotomicrografias obtidas pela MO estruturas como fibras musculares, tecido adiposo (TA) e conjuntivo denso (TCD) foram observados. Além disso, em algumas fotomicrografias foram observados poucos pontos focais de infiltrado inflamatório. Próximo ao tecido muscular foi observada a presença de TA permeado de TCD, caracterizando como um tecido capsular.

Foams of PLA/Starch and PLA/Starch/Sepiolite (SEP) with different compositions were produced. The following techniques were used in the samples characterization: i) scanning electron microscopy (SEM); ii) density (ρ) measures; iii) differential scanning calorimetry (DSC), iv) mechanical analysis (flexion and traction); v) dynamic mechanical thermal analysis (DMTA); vi) in vivo test. In the SEM images, in both foams and precursors, the interface between the phases was eminently physic with two distinct phases with gaps between them, and an increase in size of the gaps was observed in the foam. It was observed that in the samples with SEP occurred greater generation of smaller cell and more compact. This demonstrates that SEP presented, as well as the starch granules, the nucleating agent behavior. In ρ measures the lowest values were found in samples originating from the autoclave and glycerine bath, respectively. These decreases were consistent with the expansion of PLA matrix observed in the SEM images. In the DSC measurements in general, the starch addition to PLA resulted in increased Xc. This effect happened because the interface between starch and PLA be more energetic, which facilitated the crystals formation in the PLA matrix. In composites containing SEP, generally larger Xc values were observed when compared with the PLA/starch blends in the same proportions materials. This behavior is probably related to the effect of the SEP as a nucleating agent in the PLA. In the mechanical analysis, flexion and traction, with increasing starch content in the blends lower resistance and maximum deformation as the tension and rupture deformation were obtained. Additionally, the same decrease in performance was maintained for composites SEP. However, in the tensile test, these samples showed values greater than the blends. In the results observed via DMTA, in general, the addition of starch and SEP resulted in a stiffness decrease of PLA matrix, that is, E' lower values for blends and composites when compared with pure PLA samples. In the in vivo study, approved by the Ethics Committee on Animal Use the FCT/UNESP, Presidente Prudente, São Paulo, Brazil (process No. 02/2014), 18 rats Wistar (Rattus norvegicus, albino variety, Rodentia, Mammalia) were used with age of 120 days, obtained from the Universidade do Oeste Paulista (UNOESTE). The animals underwent surgical procedure for samples implantation, after 40 weeks counted from the implantation surgery date, the samples were removed. For structural analysis of removed samples and tissues SEM morphology measurements and optical microscopy (OM) were performed respectively. It was observed by SEM technique that the surfaces of post-implant samples showed a pattern coating by biological tissue with capsular morphology. In the photomicrographs obtained by OM, structures such as muscle fibers; adipose tissue (AT) and dense connective (TDC) were observed. Furthermore, in photomicrographs were observed in some few focal inflammatory infiltrate. Next to the muscle tissue was observed the presence of AT permeated by the TDC, featuring as capsular tissue.
Development of PLA/Starch and PVDF/Starch polymeric blends for applications as biomaterials
Keywords: PLA; Sepiolita; Amido